2015
DOI: 10.3111/13696998.2014.985381
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based inpatient resource utilization associated with autosomal dominant polycystic kidney disease in the US

Abstract: Although patients with ADPKD were generally healthier than patients with CKD, specific kidney function complications were more frequent. Patients with ADPKD had a higher rate of major kidney procedures, which may contribute to the high burden of ADPKD-related hospital-based inpatient resource utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In a US context, there is scant information on the burden of ADPKD from a societal perspective as prior studies estimating the costs of ADPKD in the US focused on direct healthcare costs only and did not include indirect costs [7,10,11]. Consistent with the current study, these studies found that total healthcare costs associated with ADPKD are high, particularly among patients with ESRD requiring dialysis [7,10,11].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In a US context, there is scant information on the burden of ADPKD from a societal perspective as prior studies estimating the costs of ADPKD in the US focused on direct healthcare costs only and did not include indirect costs [7,10,11]. Consistent with the current study, these studies found that total healthcare costs associated with ADPKD are high, particularly among patients with ESRD requiring dialysis [7,10,11].…”
Section: Discussionsupporting
confidence: 72%
“…Given that ADPKD is a life-long and progressive disorder, a substantial economic burden over the course of the disease is expected, including a variety of treatmentrelated and other costs [6][7][8][9][10][11][12][13]. Few studies to date have estimated direct and indirect costs among patients with ADPKD.…”
Section: Introductionmentioning
confidence: 99%
“…Of the studies that were excluded, most focused on small convenience samples of ADPKD patients that were not generalizable to a regional or national population. The resulting population-based studies [32-34] are described in detail in the Appendix.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining study [32] also focused on patients with advanced disease, defined as prevalent cases of ADPKD who received inpatient care in 390 hospitals in the USA. Inpatient resource utilization was the primary focus of this study, and the data presented provide key data on healthcare utilization patterns in ADPKD patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation